84.0k views
0 votes
Solve for x:
( x - 6 ) ^ 2 = 7

User Ergohack
by
6.4k points

2 Answers

2 votes

Answer:

uhhhh okay thank you for removing my answer

Explanation:

User Arturo Molina
by
6.3k points
5 votes

Answer: x= 6 +/- root of 7

Explanation:

1. Expand the left hand side: e.g, 3^2 = 3×3 =9

(x-6)(x-6) = 7

2. Multiply the brackets first by "separating" one of them, and take 7 to the left hand side:

x(x-6) - 6(x-6) =7

x^2 - 6x -6x +36-7=0

Simplify by adding like terms

x^2 -12x +29=0

3.Now your equation is in the form ax^2+bx + c =0, it means you can use the quadratic formula which is x= [-b +/- root of (b^2 - 4ac)]÷ 2a

Then SUBSTITUTE where:

a=1

b= -12

c=29

Therefore, x should be 6+ root of 7 OR 6- root of 7

User Narendra Rabari
by
6.3k points